Field notes contributed by Michael C. Newlon, fall 1977 - Newlon, Michael C.et al (1977)
List of birds and locations contributed by Michael C. Newlon. Field notes include an attached list of species observed by other birders. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed